PEMODELAN ANOMALI GRAVITASI DENGAN PENDEKATAN BENDA BERBENTUK SILINDER - Rahmanto, Dedi; Yulianto, Tony (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT---A  gravity  anomalies  modeling  program    has  been  made  with  the  approximation  of  cylinder shaped body  for  the case of  N anomalous bodies. This program  is named DRAVECT version 1.1. The modeling program was executed by Microsoft Visual Basic   6.0   programming language.The program was made by identifying gravity problems. Input and output data that be identified from gravity parameters, dimension and position parameters of anomalous bodies. The gravity   anomalies were calculated by  inserting synthetic data  to the  modeling  program.  The  anomaly  profiles  3  D  were  displayed  automatically,  and  the  profiles  of  gravity anomalies 2 D were made respectively. Validation test had been done by compare program result with reference. Based  on  the  graphical  qualitative  interpretation  of  gravity    anomaly  profiles  as  the  result  of  the  conducted modeling, it was obtained the characteristics of gravity anomaly of cylinder shaped body. Keyword : gravity anomalies, cylinder